2021
DOI: 10.3389/fnhum.2021.699947
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Modulation of Frontal Alpha Asymmetry - a Novel Biomarker of Mild Traumatic Brain Injury

Abstract: Objective findings of brain injury or dysfunction are typically lacking in mild traumatic brain injury (MTBI) despite prolonged post-concussion symptoms in some patients. Thus, there is a need for objective biomarkers of MTBI that reflect altered brain physiology underlying subjective symptoms. We have previously reported increased attention to threat-related stimuli in subjects with MTBI, suggesting a physiological vulnerability to depression. Vulnerability to depression has been linked with relatively greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 89 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…This scheme provides a setting where subtle alterations in emotion-attention interaction and emotional control are likely reflected in FAA, unlike during resting state FAA measurements. During active engagement of the frontal circuits, we have shown that emotional modulation of FAA (eFAA) correlates with emotionally modulated behaviors [142] and depressive symptoms [143]. This novel biomarker, eFAA, could overcome some of the weaknesses of the resting state FAA and be a more reliable biomarker of alteration in emotion-attention interaction, extending beyond depression [142,143].…”
Section: Emotional Modulation Of Faa-a Novel Biomarker For Rh Emotion-attention Interactionmentioning
confidence: 99%
See 3 more Smart Citations
“…This scheme provides a setting where subtle alterations in emotion-attention interaction and emotional control are likely reflected in FAA, unlike during resting state FAA measurements. During active engagement of the frontal circuits, we have shown that emotional modulation of FAA (eFAA) correlates with emotionally modulated behaviors [142] and depressive symptoms [143]. This novel biomarker, eFAA, could overcome some of the weaknesses of the resting state FAA and be a more reliable biomarker of alteration in emotion-attention interaction, extending beyond depression [142,143].…”
Section: Emotional Modulation Of Faa-a Novel Biomarker For Rh Emotion-attention Interactionmentioning
confidence: 99%
“…Consequently, it has potential as a biomarker for affective brain functions. Such biomarkers have shown potential applicability for assessing the impact of neuromodulation [142] and the impact of MTBI on affective neural circuits and functions [143].…”
Section: Interference Of Task Performance Due To Emotional Distractorsmentioning
confidence: 99%
See 2 more Smart Citations